The Impact of Artificial Intelligence on Genocide: Opportunities and Risks - Al-Biladi, Mohammed (Journal of Legal Sciences, 2026)
Artificial intelligence (AI) is one of the most significant technological achievements of the modern era, with its applications expanding to both military and civilian sectors. However, this remarkable innovation poses serious legal and ethical challenges, particularly concerning genocide, a grave international crime. Genocide targets a specific group based on nationality, ethnicity, race, or religion, and can be perpetrated using AI technologies through weapons, AI-equipped robots, or biased algorithms that can carry out systematic killings amounting to genocide. On the other hand, AI can play a crucial role in the early detection of genocide by analyzing big data and providing accurate information or digital evidence that supports the identification of perpetrators. This research highlights the dangers facing humanity from the use of AI technologies in crime, especially genocide, while also exploring its potential as a vital tool for crime prevention and achieving justice.